Relationship Between Sleep Quality and Primary Headache Among Employees of PT. Valeo Ac Indonesia - Simanjuntak, Harel Mega Serafine; Hutagalung, Haflin Soraya; Indri Adriztina; Sri Amelia (Journal of Society Medicine, 2024)
Introduction: Primary headaches, including migraines and tension-type headaches (TTH), are characterized by pain in the head without any underlying health issues. Poor sleep quality is a significant factor contributing to the occurrence of these headaches. Despite the prevalence of these conditions, many individuals neglect them and fail to seek appropriate treatment. This study analyzed the relationship between sleep quality and primary headache. Methods: This analytical research utilized a cross-sectional approach. Primary data were collected directly from respondents using two validated questionnaires: the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality and the Headache Screening Questionnaire (HSQ) to identify primary headache characteristics. The study included 92 employees of PT. Valeo AC Indonesia as respondents. Results: Among the 92 subjects, 32.6% were found to have poor sleep quality, while 35.9% experienced primary headaches. Tension-type headaches (TTH) were identified as the most common type of primary headache. Primary headaches were predominantly reported by individuals aged <30 years, male respondents, and those who were married. Bivariate analysis revealed a significant relationship between poor sleep quality and the occurrence of primary headaches, with a p-value of 0.015, indicating statistical significance. Conclusion: This study demonstrates a significant relationship between sleep quality and the prevalence of primary headaches among employees of PT. Valeo AC Indonesia. These findings highlight the importance of improving sleep quality as a potential strategy to reduce the occurrence of primary headaches, particularly among at-risk populations.